PENERAPAN ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT (E-CRM) GUNA MENINGKATKAN LOYALITAS PASIEN RUMAH SAKIT - Adiiba Dwikanthi; Hendri Irawan (Universitas Lampung, 2019)
The hospital is an organization that has an important role in efforts to improve public health. In running its business, the hospital continues to strive to improve services for its patients so as not to move to competitors. Rumah Sakit Ibu dan Anak (RSIA) XYZ is one of the providers of quality medical services for mothers and children. The hospital continues to strive to improve the quality of customer relations by providing the best service for its patients. Problems that arise in the hospital are related to unsatisfactory services that make patients disappointed. One of them is a fairly long procedure, which causes the patient to wait a long time to get action. An information system prototype has been designed using the concept of Electronic Customer Relationship Management (e-CRM). This concept provides the best service for patients who have not moved to competitors. System Development Life Cycle (SDLC) method used is prototyping technique. This application prototype was built using PHP programming with the MySQL database. The features contained in the prototype include the appointment of the doctor, the witness feature, the complaint feature, the askdoctor feature, and the promo feature that is useful for getting patients and improving the quality of service to maintain patient loyalty at RSIA XYZ.